ISSUES OF BANKING SYSTEM DIGITALIZATION IN UZBEKISTAN - Abduvakhidov Akmal Abdulazizovich; Kamilova Sanobar Mirdjamolovna; Eshpulatov Dostonbek Bakhodir ogli (Scholar Express Journals, 2022)
Today, the rapid development of the digital economy is considered one of the important conditions for achieving sustainable development. The digital economy and digital technologies are also rapidly entering the banking system. Digitization of banks will further improve the quality of banking services, eliminate various administrative barriers. The article discusses the mechanism of operation of modern innovations in the field of finance and their evolution, analyzes digital solutions for use in the banking sector
Keywords: digital economy; digitization; digital technologies; financial technologies